Rancang Bangun Alat Ukur Kekeruhan Air Menggunakan Fototransistor dan LED Inframerah Berbasis Arduino Uno - Nita Suliyani; Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Arif Surtono (Journal of Energy, Material, and Instrumentation Technology, 2021)
In this research, the water turbidity measurement tool based on Arduino Uno has been designed and built using phototransistors and infrared LEDs. This measuring instrument consists of a series of infrared sensors, Arduino as a process, LCD I2C as a value viewer, Micro SD as a data storage, and RTC as a timer. This study used two water samples with various concentrations. The sample used, namely distilled water plus impurities in the form of soil and ash. The distilled water used is still 100 ml with variations in the concentration of impurities ranging from 0,1-0,9 gr. Sensor test results show that the greater the turbidity level, the greater the voltage obtained. Sensor scanning ranges from 2,02 V-4,00 V for groundwater and 2,02 V-4,31 V for ash water. The reading uses a standard measuring instrument for groundwater ranging from 0 NTU to 331,4 NTU, while for ash water ranging from 0 NTU to 284,4 NTU. Data from the sensor test results in an equation used to convert the artificial measuring instrument's voltage value into a turbidity value. Then, data is taken using the same sample, so groundwater's turbidity value was obtained from 0 NTU to 318,94 NTU while for ash water from 0 NTU to 285,13 NTU. Based on the results, average accuracy for water was obtained. Soil amounted to 94,66%, while for ash water was 96,63%.